Use of organic fertilizers in Cucurbitaceae production: literature review - Zambrano-Gavilanes, Freddy (2023)
The man has adopted innumerable procedures to improve the quality of his agricultural products, as well as to mitigate the adversities that can occur in crops, looking for alternatives to improve soils, produce under controlled conditions, guarantee profitability in crops and contribute to the health of consumers. Agroecological agriculture or other expressions is the result of intensive, industrial agriculture, or the green revolution due to the negative impacts on the soil, the atmosphere and crops such as cucurbits, among which stand out: melon (Cucumis melo L.), watermelon (Citrullus lanatus T.), cucumber (Cucumis sativus L.), pumpkin (Cucurbita maxima D.), among other. The objective of this work was to develop a literature review on the use of organic fertilizers in cucurbits. It was used in the review of 56 scientific documents in English, Spanish and Portuguese, included in Web of Science, SCOPUS, Scielo, Redalyc and Latindex 2.0 from 2010 to 2023, using the keywords ¨family Cucurbitaceae¨, ¨importance of Cucurbits¨, ¨organic fertilizers¨, ¨use of organic fertilizers in Cucurbits¨, in addition Boolean operators such as ¨and¨ were used in searches with organic fertilizer and specific cucurbits. It was observed that greater use of organic fertilizer came from bovine manure in eight documents (50%). It was possible to conclude that it is possible to produce cucurbits with different organic fertilizers and that their production and quality depend on their nutritional content, as well as edaphoclimatic factors related to the crop.